Application of kinesitherapy within the process of rehabilitation of patients with Charcot-Marie-Tooth nerval amyotrophia - Rybalko, Lina; Kletsenko, Liudmyla; Vyshar, Yevheniia; Heta, Alla; Żukow, Xawery; Levkov, Anatolij; Zukow, Walery; Muszkieta, Radosław; Hagner-Derengowska, Magdalena; Smoleńska, Olga; Kindrat, Vadim (European Journal of Clinical and Experimental Medicine, 2023)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. Researching inherited polyneuropathy is vastly topical in the course of the contemporary practice of physical therapy and ergotherapy. The article unveils the results of the application of kinesitherapy in the process of rehabilitation of patients with Charcot-Marie-Tooth nerval amyotrophia. Inherited Charcot-Marie-Tooth neuropathy is a genetical disease, which is manifested with the slow reduction of the size of muscles of limbs and weakening of distal locations, is the most widespread clinical form of inherited polyneuropathies, which affect people regardless of generational and gender-based; mostly young and workable people become the objects suffering from its impact. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Description of the case. Due to the relatively low frequency of the multiplication of the disease within the population (according to the data from clinical statistics, the prevalence of all types of Charcot-Marie-Tooth amyotrophia per 100 thousand people is approximately 36 cases) four patients with Charcot-Marie-Tooth nerval amyotrophia aged in the area from 14 to 20 years took part in the research. In the course of the research, we applied the method of electroneuromyography, which provided the opportunity of detecting the rate of impulse impact via afferent and efferent ways, the duration of M-response and the number of movable entities within lower limbs. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. As a result of classes being held and carried out according to the experimental kinesitherapy study program, there was the detection of positive tendencies of changing the psychophysical state of patients, diagnosed with “Charcot- -Marie-Tooth nerval amyotrophia”.